2022
DOI: 10.1101/2022.11.10.22282089
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Portable in-clinic video-based gait analysis: validation study on prosthetic users

Abstract: Despite the common focus of gait in rehabilitation, there are few tools that allow quantitatively characterizing gait in the clinic. We recently described an algorithm, trained on a large dataset from our clinical gait analysis laboratory, which produces accurate cycle-by-cycle estimates of spatiotemporal gait parameters including step timing and walking velocity. Here, we demonstrate this system generalizes well to clinical care with a validation study on prosthetic users seen in therapy and outpatient clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Interest in video-based, markerless gait analysis has accelerated rapidly. Previous studies have used various approaches to move quantitative clinical gait analysis outside of the laboratory or research center and directly into the home or clinic 5,6,[13][14][15]17 . Here, we aimed to develop a single approach that addressed several outstanding needs, including the needs to accommodate multiple different types of environments/viewing perspectives, use of datasets in multiple clinical populations with gait impairment, measurement of both spatiotemporal gait parameters and lower extremity two-dimensional kinematics, and measurement of withinparticipant changes in gait.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interest in video-based, markerless gait analysis has accelerated rapidly. Previous studies have used various approaches to move quantitative clinical gait analysis outside of the laboratory or research center and directly into the home or clinic 5,6,[13][14][15]17 . Here, we aimed to develop a single approach that addressed several outstanding needs, including the needs to accommodate multiple different types of environments/viewing perspectives, use of datasets in multiple clinical populations with gait impairment, measurement of both spatiotemporal gait parameters and lower extremity two-dimensional kinematics, and measurement of withinparticipant changes in gait.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is a need for validation in additional adult and pediatric clinical populations, as previous work has shown that existing pose estimation algorithms have difficulty with tracking patient populations with anatomical structures that likely differ significantly from the images used to train the algorithms 13 . Thirteen of the participants with stroke used a cane; we did not observe instances where OpenPose mistakenly identified the cane as a limb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that the robust triangulation approach was described in a paper on multiview self-supervised learning (SSL) [27], where the information between views is used to improve the geometric consistency between 2D keypoint detectors, and we plan to implement this for fine-tuning keypoint detectors. This would have the added benefit of allowing learning from a diverse clinical population, which can address limitations we have previously noted such as tracking the location of prosthetic limbs [26]. Keypoint detectors would also be improved for biomechanics by learning denser keypoints over the trunk, as their absence can limit understanding pelvis movement and reconstructing hip angles without training additional models to mitigate this [3].…”
Section: Discussionmentioning
confidence: 99%
“…However, the DLT is sensitive to outliers, which will occur if another person occludes the view and has their joints detected, or if a joint is misdetected in one view, such as for people with limb differences like prosthetic users [26]. A common approach to outlier rejection in 3D reconstruction is RANSAC, but this is a slow algorithm.…”
Section: Data Acquisitionmentioning
confidence: 99%